2022
DOI: 10.3390/coatings12050667
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of a Cr-Al Coating Deposited on 304 Austenitic Stainless Steel by Multi-Arc Ion Plating in Liquid Lead–Bismuth Eutectic

Abstract: In this paper, a Cr-Al coating was deposited using multi-arc ion plating (MAIP) on 304 austenitic stainless steel. The Cr-Al-coated sample was treated by vacuum annealing at 600 °C for 12 h, and its corrosion behaviors against static LBE were carefully evaluated by SEM, EDS and XPS at a temperature of 600 °C for 1000 h, compared with an uncoated sample. The results showed that the uncoated sample was corroded by the dissolution and oxidation of LBE severely; a duplex-layered oxide layer consisting of an outer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Similarly, Duran et al discovered that poly(N-vinyl carbazole) films can provide anodic protection and reduce the corrosion rate of 304 SS by six times in sulfuric acid solution [ 11 ]. Additionally, Sun et al deposited Cr–Al coating on 304 SS and found it to have good corrosion resistance under static lead–bismuth eutectic [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Duran et al discovered that poly(N-vinyl carbazole) films can provide anodic protection and reduce the corrosion rate of 304 SS by six times in sulfuric acid solution [ 11 ]. Additionally, Sun et al deposited Cr–Al coating on 304 SS and found it to have good corrosion resistance under static lead–bismuth eutectic [ 12 ].…”
Section: Introductionmentioning
confidence: 99%